GPAT4 sustains endoplasmic reticulum homeostasis in endocardial cells and safeguards heart development - Tianyang Zhao; Kuipei Jin; Xiaodong Wang; Xiong Su; Youjun Wang; Mingming Gao; Wen Luo; Hongyuan Yang; Zhongzhou Yang (Nature Communications)
Abstract The endocardium plays a pivotal role in governing myocardial development, and understanding the intrinsic regulatory insights will help apprehend pathological cardiomyopathy. Glycerol-3-phosphate acyltransferase 4 (GPAT4) is an endoplasmic reticulum (ER) membrane anchored protein. While the role of GPAT4 in glycerophospholipid biosynthesis is well established, its function in the ER is less explored. Here, we generate Gpat4 global and tissue-specific knockout mice and identify the essential role of GPAT4 in endocardial development. Deficiency of GPAT4 provokes endocardial ER stress response and enhances ER-mitochondrial (ER-mito) communications, leading to mitochondrial DNA (mtDNA) escape. As a result, the cGAS-STING pathway is triggered to stimulate type-I-interferon response, which affects heart development. Finally, abolishment of the cGAS-STING-type-I-interferon pathway rescues the heart defects of Gpat4 deletion mice. These findings uncover the pivotal role of GPAT4 in the maintenance of ER homeostasis during endocardial and heart development. Meanwhile, this study highlights the importance of the cGAS-STING pathway in cardiac organogenesis.